Challenges in Collecting Personal Network Data: The Nature of Personal Network Analysis - Wellman, Barry (Field methods, 2007)
Discusses personal network analysis as opposed to network analysis, thus analyzing the social network of an individual versus that of the individual's communal association. Divides the subjects into two camps, that of the main subject, the ego, and those of the ego's relationships, the alters. Asks whether the relationships themselves or the networks to which they belong are the main points of support for the egos, and to which degree, that understanding may occur regarding which resources and forms of support are given and whether by either family, friends, acquaintances, neighbors, etcetera, thus weighing these different alter-types against each other. Questions of methodology and the problems they face are explored -as in the frequency of contact between egos and alters and clusters of alters and the dynamics they play with each other and more so with the ego. Further, considers quantity of alters that the average American has, how often contact is made between each contact, and the number of meaningful alters, vice those that are of a more incidental nature. Briefly mentions use of a so-called 'name generator' in the research, along with asking questions about reciprocity amongst the subjects. Lastly states that the structure of an ego's networks has largely been ignored due to unreliability and time constraints. References. S. Fullmer